Modelling of puncture responses in papaya using finite element analysis - Zulkifli, Nurazwin (2022)
Monitoring of impact damage of papaya due to punctures and cuts caused by excessive loading is a significant problem in papaya production. Therefore, this study aims to develop a finite element (FE) model to determine the puncture responses of Exotica papayas during storage. As a first step to modelling the puncture responses of papaya during storage, the physiochemical and puncture properties were analysed. The fruits were used to measure the physicochemical properties (i.e colour, weight, dimensions, density, moisture content (MC), total soluble solids (TSS), pH) and puncture properties (i.e., bioyield force, apparent elastic modulus, and mean force). The colour and TSS were best regressed with all puncture properties with the coefficient of determination (R2) more than 0.85. Through the combination of FE analysis and optimisation procedure, the constitutive properties of flesh and skin were obtained. The FE data showed strong agreement with experimental data with R2 values obtained of 0.87 and 0.88 for FE compression and tensile models, respectively. Throughout the 16 days' storage durations, the FE model was able to predict a decrease of 54.28% and 71.24% in failure stress of flesh and skin, respectively. A three-dimensional (3D) FE model to simulate the probe-papaya interaction during the puncture test was then developed. The fruit model was presented as a multi-body system, and the constitutive properties of skin and flesh were used for the material model. The resulting force-deformation of the FE data was compared with the experimental data for the validation of the FE puncture model. Sensitivity checks were also done to evaluate the robustness of the FE model using the different values of constitutive properties of flesh and skin. Results indicated that the model was able to predict the decrease in bioyield force of 39% when the papaya was stored at 12 ± 1°C for 16 days. This study also suggested that the skin contributes more than 20% to the overall stiffness of the whole papaya. The extreme values of 22.3N proved this detection for the bioyield force measured in the FE model when performing the sensitivity checks on skin properties, instead of 16.8N obtained during the sensitivity checks on flesh properties. In conclusion, the FE model developed in this study potentially serves as a reliable prediction method to predict the puncture properties of papaya. The simulation and modelling of the different loading cases using the FE method can be beneficial to predict failure stress in papaya, which can occur during postharvest handling operations.